1998
DOI: 10.1046/j.1365-2435.1998.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated N deposition on understorey vegetation of a boreal coniferous forest

Abstract: Summary 1.We report the short-term effects of simulated nitrogen (N) deposition on the understorey of a boreal forest in northern Sweden. Doses of 15 N double-labelled NH 4 NO 3 (0·5, 12·5, 25·0 and 50·0 kg N ha -1 ) were applied to 1 m 2 plots in the summer of 1995 and plants were harvested the following autumn. 2. No significant treatment effects were found in either above-or below-ground biomass which was distributed as follows: the ericaceous shrub Vaccinium myrtillus contributed 76%, the grass Deschampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
3
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 32 publications
(43 reference statements)
9
76
3
3
Order By: Relevance
“…In this case, the available carbon is invested in growth rather than in defence. It is well established that nitrogen addition increases nitrogen concentrations in heather, C. vulgaris (Berdowski and Siepel 1988;Duncan et al 1994;Hartley et al 1995;Carrol et al 1999;Gordon et al 1999) and other ericaceous plants (Mallik 1996;Prescott et al 1993;Nordin et al 1998). However, the expected decrease in total phenolics or condensed tannin levels due to solely nitrogen additions has not yet been empirically shown either in the greenhouse or in the field (Iason and Hester 1993;Hartley et al 1995;Kerslake et al 1998;Bradley et al 2000;Alonso et al 2001;Hansen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the available carbon is invested in growth rather than in defence. It is well established that nitrogen addition increases nitrogen concentrations in heather, C. vulgaris (Berdowski and Siepel 1988;Duncan et al 1994;Hartley et al 1995;Carrol et al 1999;Gordon et al 1999) and other ericaceous plants (Mallik 1996;Prescott et al 1993;Nordin et al 1998). However, the expected decrease in total phenolics or condensed tannin levels due to solely nitrogen additions has not yet been empirically shown either in the greenhouse or in the field (Iason and Hester 1993;Hartley et al 1995;Kerslake et al 1998;Bradley et al 2000;Alonso et al 2001;Hansen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Scandinavia) increasingly apply fertilizers to forests (Lindkvist et al 2011). These two types of anthropogenic N inputs can have numerous consequences in N-limited boreal forests, such as increase net primary productivity and aboveground carbon (C) stocks (De Vries et al 2006;Gundale et al 2014), alter species composition and community structure (Bobbink et al 1998 and references therein; Nordin et al 1998;Strengbom et al 2003;Nordin et al 2006), and reduce diversity (Nordin et al 2005;Bobbink et al 2010;Meunier et al 2016). While impacts of N enrichment on aboveground properties are well studied, relatively little is known about how soil processes respond to N enrichment (but see e.g.…”
mentioning
confidence: 99%
“…Springer et al (119) showed that calcium levels and rust disease are inversely related; unusual plant communities associated with serpentine outcrops may thus be particularly vulnerable to disease due to low calcium levels. In contrast, disease levels often increase as nitrogen is added to an environment (87,91,120); such patterns are also known with agricultural crops. Strengbom et al (120) explored the relationship between nitrogen addition and disease in boreal forests known to be nitrogen limited (Fig.…”
Section: Community and Ecosystem Ecologymentioning
confidence: 99%